Relación entre los factores institucionales y el emprendimiento: Análisis mediante técnicas cuantitativas - Román Salmerón Gómez; Samuel Gómez Haro (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2012)
– The majority of published studies about the relation between institutional and entrepreneurial factors lack of an adequate empirical study. Due to the importance that the institutional environment has acquired in the last few years, we consider necessary a rigorous analysis using quantitative statistical techniques. The aim of this paper is the empirical analysis of the relationship between institutional and entrepreneurial orientation Spanish company, based on theoretical and empirical identification of regulatory, cognitive and normative dimensions for the institutional environment and the dimensions of innovation, risk assumption, proactivity, and autonomy to analyze the entrepreneurial behavior.
Keywords: C13; C38; 330; entrepreneurial activity; institutional environment; factorial analysis; regression